Implementasi Program Dana Talangan Haji Khusus Antrian 7 Tahun dengan Program Dana Talangan Haji di BMT Mitra Mandiri Jawa Tengah - Khosiah, Sulatin; Prastiwi, Iin Emy; Marimin, Agus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
This research aims to a) How to implement the 7 Year Special Queue Hajj Bailout Fund Program with the Hajj Bailout Fund Program at BMT Mitra Mandiri Central Java. b) How is the Implementation of the 7 Year Special Queue Hajj Bailout Fund Program from an Islamic perspective. The research results show that the stages of the mechanism for obtaining Hajj bailout funds at BMT Research Partners are qualitative research using interview and observation data collection techniques. There were 2 informants in this study. Mandiri Wonogiri demonstrated an adequate level of transparency and detail. Prospective Hajj pilgrims who have adequate financial capabilities, especially in terms of income, financial stability and ability to save, have a greater chance of meeting the requirements and receiving Hajj bailout funds from financial institutions such as BMT Mitra Mandiri Wonogiri. The 7 Year Hajj Queue bailout program organized by BMT Mitra Mandiri Wonogiri has had a positive impact in facilitating prospective Hajj pilgrims. The main challenges faced are limited funding, a significant increase in demand, and the level of public understanding of the program.